Граматичні читання – V - Загнітко, А.; Ситар, Г.; Коваленко, Є. (Iнститут української мови НАН України, 2009)
There is an information about the International scientific and practical conference “Grammatical reading-matter — V” which took place on 5—6 February 2009 at the chair of Ukraine and applied lingustics (Donetsk national University).